2016
DOI: 10.13189/ujeee.2016.040202
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Magnetic Field from Electrical Appliances in EEE Classrooms of Southeast University Bangladesh

Abstract: The aim of this survey is to investigate whether the Electromagnetic Fields (EMF) emitted from various air conditioners and switch boards affect the students, faculties and employees. There is a standard threshold value recommended by World Health Organization (WHO) for both electric and magnetic fields. Electro-Magnetic Fields commonly known as Non Ionizing Radiation is emitted from high power transmission lines, computer monitor/video display unit, radio waves of different frequencies (extremely low frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Furthermore, a review was carried out on NIR, harmful consequences of NIR from mobile/cell phone and towers [47]. Inspections depicting the magnetic fields emitted by various sources like laboratory electronic and electrical appliances and instruments (pharmacy and textile laboratories, computer science and engineering (CSE), and electrical and electronic engineering (EEE) laboratories and classrooms) in Southeast University were performed [48]- [54]. Additionally electrical equipment and laboratory facilities in electronics and telecommunication engineering (ETE) and CSE laboratories of Daffodil International University (DIU), Bangladesh were investigated [55], [56].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a review was carried out on NIR, harmful consequences of NIR from mobile/cell phone and towers [47]. Inspections depicting the magnetic fields emitted by various sources like laboratory electronic and electrical appliances and instruments (pharmacy and textile laboratories, computer science and engineering (CSE), and electrical and electronic engineering (EEE) laboratories and classrooms) in Southeast University were performed [48]- [54]. Additionally electrical equipment and laboratory facilities in electronics and telecommunication engineering (ETE) and CSE laboratories of Daffodil International University (DIU), Bangladesh were investigated [55], [56].…”
Section: Introductionmentioning
confidence: 99%
“…Haque et al [31]- [33]; and Quamruzzaman et al [34], [35] performed various works on measurement of magnetic fields emitted from electrical appliances, laboratory equipment, switchboards and air conditioners in various laboratories and classrooms of some universities in Bangladesh. They found that many of the emission in the classrooms and laboratories are beyond the threshold limit especially from the air conditioners.…”
Section: Introductionmentioning
confidence: 99%